Laminate, optical element, and method for producing laminate
By adopting a multi-layer low-refractive index film structure, optimizing the pore characteristics of the first and second layers, the existing anti-reflection films have solved the shortcomings in anti-reflection performance and mechanical strength, and efficient light reflection suppression and mechanical performance improvement have been achieved.
Patent Information
- Application Number
- CN202510107242.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-28
- Filing Date
- 2021-02-01
- Publication Date
- 2025-03-14
AI Technical Summary
The existing anti-reflection films still have room for improvement in improving anti-reflection performance, especially in the pore quantitative state and adhesive filling rate, resulting in a high refractive index.
At least two layers of low refractive index membrane structure are adopted, wherein the first and second layers contain hollow particles and binder, respectively, and the porosity and porosity of the first layer meet certain conditions to achieve low refractive index and high anti-reflection properties.
The high anti-reflection performance of the low refractive index film is achieved, the reflectivity of light is reduced, and the mechanical strength and light transmission performance of the film are improved.
Smart Images

Figure CN119620253A_ABST
Abstract
Description
[0001] This application is a divisional application, and the Chinese national application number of the application to which it is directed is 202180014243.9, the application date is February 1, 2021, and the name of the invention is "Low refractive index film, laminate, optical element, windproof material and display device". Technical Field
[0002] The present invention relates to a low refractive index film, a laminate, an optical element, a windproof material and a display device. Background Art
[0003] In the past, it is known that there is an anti-reflection film which suppresses the reflection of light from the surface of transparent objects or substrates by applying a material having a specific refractive index to them. In particular, in the fields or uses of optical elements such as lenses or filters, windows or structural materials used in buildings, windshields for automobiles, helmets or goggles, etc., it is important to form an anti-reflection film on the surface in order to suppress the reflected light from their surfaces and increase the amount of light passing through these objects or substrates. For example, the reflectivity of one surface of glass is usually about 4 to 5%. Therefore, for an object composed of plate-shaped glass, the overall reflectivity considering the reflection of the surface and the reflection of the back can be 8 to 10%. The reflected light from the surface of a lens made of glass used with an imaging device such as a camera is repeatedly reflected or refracted through the device or other lens surfaces, which may cause undesirable phenomena such as ghosting or flare. Therefore, it is important to form an anti-reflection film on the surface of an object or substrate that performs functions such as transmission or refraction of light to suppress the reflection of the surface.
[0004] According to the theory of light reflection, by making the refractive index of the material constituting the anti-reflection film smaller than the refractive index of the substrate of the coating (ideally, the square root of the refractive index of the object coated with the film), it is expected that the reflected light can be easily reduced. However, among materials composed of a single substance, there is no material with a sufficiently low refractive index. In the past, there were the following structures: a multilayer film structure formed by laminating a plurality of layers with different refractive indices; a film structure including a so-called low refractive index film, which contains a substance such as hollow particles that can produce an effect of reducing the refractive index, and can reduce the refractive index of the entire film.
[0005] For example, Patent Document 1 describes an antireflection film formed by bonding hollow particles with a binder. The binder contains a particle with a cross-sectional area of less than 1000 nm. 2 The pore and cross-sectional area is 1000nm 2 The cross-sectional area of the adhesive is 1000nm. 2 The number of pores above 1 μm is relative to the cross-sectional area of the adhesive. 2 10 / μm 2In the example, an antireflection film was formed on the glass substrate BK7, and the refractive index of the antireflection film was 1.27.
[0006] In addition, Patent Document 2 describes an optical element having an anti-reflection film formed on a substrate. The anti-reflection film includes a low refractive index layer formed by bonding hollow particles having cavities inside with each other using an adhesive. The low refractive index layer includes a first layer as the outermost layer, and a second layer adjacent to the first layer and located on the substrate side. The filling rate of the adhesive in the first layer is lower than the filling rate of the adhesive in the second layer.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2012-108320
[0010] Patent Document 2: Japanese Patent Application Publication No. 2013-033124 Summary of the invention
[0011] Problems to be solved by the invention
[0012] According to Patent Document 1, the quantitative state of the pores in the portion of the antireflection film located near the glass substrate BK7 is uncertain. On the other hand, according to Patent Document 2, the filling rate of the binder in the second layer is high, and there is no record of the presence of pores in the second layer. Therefore, the refractive index of the second layer tends to become higher.
[0013] Under such circumstances, there is room for further research in terms of improving antireflection performance in the techniques described in Patent Documents 1 and 2. Therefore, the present invention provides a novel low refractive index film that is advantageous in terms of exerting high antireflection performance.
[0014] Means for solving problems
[0015] The present invention provides a low refractive index film, which is a low refractive index film having at least a first layer and a second layer adjacent to the first layer, wherein:
[0016] The low refractive index film has a refractive index of 1.01 or more and 1.30 or less.
[0017] The first layer and the second layer contain hollow particles and a binder, respectively.
[0018] The first layer has a thickness that is less than half the thickness of the low refractive index film and less than 200 nm,
[0019] The first layer has pores that satisfy at least one of the following conditions (I) and (II).
[0020] (I) In the cross section of the first layer, there is a 1000 nm 2 The number density of the above pores with a cross-sectional area of 5 / μm 2 Above 100 / μm 2 the following.
[0021] (II) A ratio of the cross-sectional area of the pores in the cross-section to the area of the cross-sectional area of the first layer is 5% to 70%.
[0022] In addition, the present invention provides a laminate, wherein:
[0023] The laminate comprises a substrate and the low refractive index film in this order.
[0024] The first layer is closer to the substrate than the second layer.
[0025] Effects of the Invention
[0026] The low refractive index film is advantageous in that it can exhibit high antireflection performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a cross-sectional view showing an example of the laminate of the present invention.
[0028] Figure 2A This is a cross-sectional view showing another example of the laminate of the present invention.
[0029] Figure 2B This is a cross-sectional view showing still another example of the laminate of the present invention.
[0030] Figure 2C This is a cross-sectional view showing still another example of the laminate of the present invention.
[0031] Figure 2D This is a cross-sectional view showing still another example of the laminate of the present invention.
[0032] Figure 3 This is a scanning transmission electron microscope (STEM) photograph showing a cross section of the laminate of Example 1.
[0033] Figure 4 This is a diagram showing a STEM photograph of a cross section of the laminate of Example 1 in which pores are colored black. DETAILED DESCRIPTION
[0034] The following describes the embodiments of the present invention with reference to the accompanying drawings. It should be noted that the following description relates to the illustration of the present invention, and the present invention is not limited to the following embodiments. In this specification, "anti-reflection" means having the function of preventing the reflection of light from the surface, or having the function of reducing the reflection compared to the absence of the anti-reflection structure even if the reflection does not disappear, and "film" can be understood to have the same meaning as film, coating and layer.
[0035] like Figure 1 As shown, the low refractive index film 10 is a film formed along the surface of the substrate 20. The low refractive index film 10 includes a first layer 11 and a second layer 12. The first layer 11 is located on the proximal side relative to the substrate 20 in the thickness direction of the low refractive index film 10. The second layer 12 is adjacent to the first layer 11 in the thickness direction of the low refractive index film 10 and is located on the distal side relative to the substrate 20. The low refractive index film 10 has a refractive index of not less than 1.01 and not more than 1.30. The "refractive index" in this specification refers to an absolute refractive index, for example, equivalent to a measured value using the D line of sodium at 25°C. The refractive index of the low refractive index film 10 can be determined, for example, by measurement based on reflectivity spectroscopy.
[0036] "Substrate" is an article or part of an article coated with a low refractive index film or an anti-reflection film. "Substrate" is, for example, but not limited to, optical elements such as lenses, reflectors, prisms, diffusers, flat microlens arrays, polarizing elements, diffraction gratings, holograms, light modulating elements, light deflecting elements, and filters (including acousto-optic elements), solid-state imaging devices, windows or windshields of buildings or cars, light-transmitting shields such as helmets and goggles, or display devices such as display screens and screens. The coated surface of the "substrate" can be a flat surface, a curved surface, or a concave-convex surface.
[0037] like Figure 1 As shown, the first layer 11 and the second layer 12 contain hollow particles 13 and a binder 14, respectively. The first layer 11 has a thickness of less than half the thickness of the low refractive index film 10 and less than 200 nm. The first layer 11 has pores 15 in a manner that satisfies at least one of the following conditions (I) and (II). It should be noted that the pores 15 are spaces that exist inside or at the interface of the low refractive index film 10 and are not occupied by the hollow particles 13 and the binder 14. For example, the internal space of the hollow particles 13 does not belong to the pores 15. For example, air exists in the pores 15.
[0038] (I) In the cross section S1 of the first layer 11, there is a 1000 nm 2 The number density ρv1 of the pores 15 with a cross-sectional area above is 5 / μm 2 Above 100 / μm 2 the following.
[0039] (II) The ratio (Av1 / At1) of the cross-sectional area (Av1) of the voids 15 present in the cross section S1 to the area (At1) of the cross section S1 of the first layer 11 is 5% to 70%.
[0040] By making the first layer 11 satisfy at least one of the conditions (I) and (II), the quantitative state of the pores 15 in the first layer 11 becomes a desired state, and the first layer 11 in the low refractive index film 10 easily has a low refractive index. As a result, the low refractive index film 10 easily exhibits high anti-reflection performance. The pores 15 can be formed inside the first layer 11 or at the interface between the low refractive index film 10 and other components.
[0041] Regarding condition (I), "having 1000nm 2 The cross-sectional area of the pore 15" mentioned above means that the cross-sectional area of one pore 15 defined by the boundary between the pore 15 and the surrounding material of the pore 15 in the cross section S1 is 1000 nm. 2 When the number density ρv1 is obtained, the area surrounded by a rectangle having a length (width) of 1000 nm (1 μm) along the surface of the substrate 20 and a height corresponding to the thickness d1 of the first layer 11 in the cross section of the laminate including the first layer 11 is taken as the cross section S1, and the pores having a length (width) of 1000 nm (1 μm) existing inside the rectangle are calculated. 2 The number of pores 15 with a cross-sectional area above is counted. The number density ρv1 is calculated by dividing the number by the area At1 of the section S1. It should be noted that when calculating the number density ρv1, the pores completely contained in the area of the section S1, the pores in which a part of the surface of the substrate or the base layer becomes a part of the boundary, and the pores only partially contained in the section S1 are also counted. By setting the number density ρv1 to 5 / μm 2 As described above, the first layer 11 in the low refractive index film 10 is likely to have a low refractive index. In addition, even if the difference between the expansion coefficient of the substrate 20 and the expansion coefficient of the low refractive index film 10 is large, it is easy to reduce the risk of cracks or splits in the low refractive index film 10 due to temperature changes. The number density ρv1 is preferably 6 / μm 2 More preferably 8 / μm 2 More preferably, 10 / μm 2 By setting the number density ρv1 to 100 / μm 2 The low refractive index film 10 can easily have the desired mechanical strength. In addition, it is easy to prevent the scattering of incident light such as visible light from increasing, and it is easy to keep the haze of the article equipped with the low refractive index film 10 low. The number density ρv1 is preferably 99 / μm 2 Below, more preferably 90 / μm 2 Below, more preferably 85 / μm 2The number density ρv1 can also be 75 / μm 2 Below, 50 / μm is also possible 2 the following.
[0042] Regarding the condition (II), the ratio (Av1 / At1) expressed as a percentage is also referred to as the porosity Vv1 [%]. When the porosity Vv1 is obtained, the pores with a size of 1000 nm existing in the cross section S1 are 2 The sum of the areas of the pores 15 with the cross-sectional area above is set as Av1. It should be noted that, when obtaining the sum of the areas Av1 of the pores 15, Av1 is obtained by considering the area of the pores completely contained in the area of the cross section S1 and the area of the part of the pores only partially contained in the area of the cross section S1 that exists in the area of the cross section S1. By making the porosity Vv1 5% or more, the first layer 11 in the low refractive index film 10 is easy to have a low refractive index. In addition, even if the difference between the expansion coefficient of the substrate 20 and the expansion coefficient of the low refractive index film 10 is large, it is easy to reduce the risk of cracks or splits in the low refractive index film 10 due to temperature changes. The porosity Vv1 is preferably higher than 5%, more preferably 9% or more, and further preferably 10% or more. By making the porosity Vv1 70% or less, the low refractive index film 10 is easy to have the desired mechanical strength. The porosity Vv1 is preferably lower than 70%, more preferably 65% or less. The porosity Vv1 may be 50% or less, or 30% or less.
[0043] When the first layer 11 satisfies the above condition (I), the number density ρv1 is higher than, for example, 1000 nm in the cross section S2 of the second layer 12 extending along the surface of the substrate 20. 2 The number density ρv2 of the pores 15 with a cross-sectional area of 1000 nm (1 μm) or more is calculated. Thus, the first layer 11 in the low refractive index film 10 is more likely to have a low refractive index more reliably. When the number density ρv2 is calculated, the number density ρv2 of the pores 15 with a cross-sectional area of 1000 nm (1 μm) or more is calculated. 2 The number of pores 15 with a cross-sectional area of 1000 nm or more is counted. The number density ρv2 is obtained by dividing the number by the area At2 of the section S2. It should be noted that, when obtaining the number density ρv2, in addition to the pores completely contained in the area of the section S2, the pores that constitute part of the boundary of the surface opposite to the surface of the second layer 12 that is in contact with the first layer 11 and the pores that are only partially contained in the area of the section S2 are also counted. 2The total area of the pores 15 having the above cross-sectional area is designated as Av2. When obtaining the total area Av2 of the pores 15, Av2 is obtained by considering the area of the pores completely included in the region of the cross-section S2 and the area of the portion existing in the region of the cross-section S2 among the pores only partially included in the region of the cross-section S2.
[0044] When the first layer 11 satisfies the condition of the above (II), the ratio (Av1 / At1) is, for example, higher than the ratio (Av2 / At2). The ratio (Av2 / At2) is a value expressed as a percentage of the cross-sectional area Av2 of the pores 15 existing in the cross-section S2 of the second layer 12 with respect to the total area At2 of the cross-section S2 of the second layer 12 having a length of 1000 nm extending along the surface of the substrate 20. Thus, the first layer 11 in the low-refractive-index film 10 can more reliably have a low refractive index.
[0045] The cross-section S1 and the cross-section S2 are typically cross-sections formed by cutting the low-refractive-index film 10 along a plane parallel to the normal of the surface of the substrate 20. The cross-sections shown in the cross-sectional views or electron micrographs in the drawings correspond to such cross-sections.
[0046] The first layer 11 and the second layer 12 are distinguished by an interface surface orthogonal to the normal of the surface of the substrate 20. Typically, in the thickness direction of the low-refractive-index film 10, the portion closer to the substrate 20 than the interface surface corresponds to the first layer 11, and the portion farther from the substrate 20 than the interface surface corresponds to the second layer 12. It should be noted that this interface surface may actually exist or may be imaginary. For example, the adhesive 14 may form a continuous phase in the first layer 11 and the second layer 12.
[0047] The low-refractive-index film 10 has a thickness dt of, for example, 70 nm or more. When, for example, 70 nm ≤ dt ≤ 400 nm, the thickness d1 of the first layer 11 is equal to dt / 2. In addition, when, for example, 400 nm < dt, the thickness d1 of the first layer 11 is equal to 200 nm. By making the first layer 11 having such a thickness satisfy at least one of the conditions (I) and (II), the low-refractive-index film 10 can more reliably exhibit high antireflection performance.
[0048] The refractive index of the low-refractive-index film 10 is preferably 1.05 or more and 1.28 or less, more preferably 1.10 or more and 1.25 or less.
[0049] The material of the adhesive 14 is not limited to a specific material. The material of the adhesive 14 is, for example, a material that satisfies desired characteristics in terms of environmental resistance, abrasion resistance, and adhesion to the substrate. In addition, the material of the adhesive 14 is preferably a material having high transparency to light in a specific wavelength range used in an article having the low refractive index film 10. The specific wavelength range used in an article having the low refractive index film 10 may exist in the visible light region or the near infrared region.
[0050] The adhesive 14 includes, for example, silicon dioxide, silsesquioxane, or a mixture of silicon dioxide and silsesquioxane. In this case, the wavelength range in which transparency can be ensured in the visible light region in the adhesive 14 is easily widened. In addition, the refractive index of the adhesive 14 can be reduced to a certain extent.
[0051] The adhesive 14 may contain a specific curable resin, for example, depending on the type of the substrate 20 or the performance required of the article having the low refractive index film 10. The curable resin is in a liquid state when applied to the surface of the substrate 20, but is cured by heating, light energy irradiation, etc. after application, thereby facilitating the manufacture of the low refractive index film 10. Examples of the curable resin are phenol resin, epoxy resin, melamine resin, unsaturated polyester resin, polyurethane resin, polyimide resin, acrylic resin, and silicone resin.
[0052] When the binder 14 includes silicon dioxide, silsesquioxane, or a mixture of silicon dioxide and silsesquioxane, for example, 1%≤W Si ≤60% and 5% ≤W Sq ≤90% of at least one of the conditions. Si W is the ratio of the mass of silicon dioxide contained in the binder 14 to the mass of the solid content of the low refractive index film 10. Sq W is the ratio of the mass of silsesquioxane contained in the binder 14 to the mass of the solid content of the low refractive index film 10. It is preferred to satisfy 5% ≤ W Si ≤60% and 8% ≤W Sq ≤80%, preferably 8%≤W Si ≤30% and 10% ≤W Sq ≤60% of at least one of the conditions.
[0053] When the adhesive 14 contains silica, silsesquioxane, or a mixture of silica and silsesquioxane, the condition of 5% ≤ Wb ≤ 90% is satisfied, for example. Wb is the ratio of the sum of the mass of silica and the mass of silsesquioxane contained in the adhesive 14 to the mass of the solid content of the low refractive index film 10. Preferably, the condition of 10% ≤ Wb ≤ 85% is satisfied, and more preferably, the condition of 20% ≤ Wb ≤ 80% is satisfied. The silica in the adhesive 14 is obtained, for example, by the hydrolysis and polycondensation of a tetrafunctional alkoxysilane. The silsesquioxane in the adhesive 14 is obtained, for example, by the hydrolysis and polycondensation of a trifunctional alkoxysilane.
[0054] The hollow particles 13 are typically particles having pores defined by shells. When the low refractive index film 10 contains the hollow particles 13, the refractive index of the low refractive index film 10 can be easily reduced.
[0055] The average particle size d of the hollow particles 13 e The average particle size d of the hollow particles 13 is not limited to a specific value. e For example, the average particle size d is 20 nm or more and 100 nm or less. e When the average particle size d is 20 nm or more, the pores inside the hollow particles 13 are likely to have a desired volume. As a result, the refractive index of the low refractive index film 10 is likely to be reduced. e The average particle size d of the hollow particles 13 is 100 nm or less, so that light scattering is not likely to increase. e For example, it is the average particle diameter in the particle size distribution based on the number.
[0056] The average particle size d of the hollow particles 13 e The diameter is preferably 25 nm to 90 nm, and more preferably 30 nm to 80 nm.
[0057] The material of the shell of the hollow particle 13 is not limited to a specific material. Examples of the material of the shell of the hollow particle 13 are inorganic compounds such as SiO2, ZrO2, and MgF2, fluorine compounds such as polytetrafluoroethylene (PTFE) and tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), and polymers forming resins. The material of the shell of the hollow particle 13 preferably has a low refractive index, for example, a refractive index lower than the refractive index of SiO2.
[0058] The thickness of the shell of the hollow particle 13 is not limited to a specific value. The thickness of the shell of the hollow particle 13 is, for example, 5 nm to 20 nm, preferably 10 nm to 20 nm.
[0059] The ratio Whp [%] of the mass of the hollow particles 13 to the mass of the solid components of the low refractive index film 10 is not limited to a specific value. The ratio Whp is, for example, 5% or more and 90% or less, preferably 10% or more and 85% or less, and more preferably 20% or more and 80% or less.
[0060] The relationship between the content of the hollow particles 13 and the content of the binder 14 in the low refractive index film 10 is not limited to a specific relationship. The low refractive index film 10 satisfies, for example, the condition of 0.2 < Wb / Whp < 20. By satisfying the condition of Wb / Whp < 20, the refractive index of the low refractive index film 10 is likely to decrease. In addition, even if the difference in the coefficient of thermal expansion between the substrate 20 and the low refractive index film 10 is large, it is not easy for the low refractive index film 10 to crack or split due to temperature changes. By satisfying the condition of 0.2 < Wb / Whp, the low refractive index film 10 is likely to have the desired mechanical strength, and it can be expected that the low refractive index film 10 is not easily damaged or peeled off.
[0061] The low refractive index film 10 preferably satisfies the condition of 0.3 < Wb / Whp < 15, more preferably satisfies the condition of 0.4 < Wb / Whp < 12, and further preferably satisfies the condition of 0.5 < Wb / Whp < 10.
[0062] The low refractive index film 10 may also contain functional components such as a light absorber as needed. Thereby, the low refractive index film 10 can exhibit an additional function corresponding to the functional component. Examples of the light absorber are an ultraviolet absorber and an infrared absorber. The ultraviolet absorber is not limited to a specific ultraviolet absorber. Examples of the ultraviolet absorber are benzophenone-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, and triazine-based ultraviolet absorbers. Examples of the infrared absorber are not limited to a specific infrared absorber. Examples of the infrared absorber are squarylium-based infrared absorbers, diimmonium-based infrared absorbers, cyanine-based infrared absorbers, phthalocyanine-based infrared absorbers, azo-based infrared absorbers, and phosphoric acid-metal compounds containing phosphoric acid derivatives such as phosphonic acid and phosphoric acid esters and metal components such as copper.
[0063] As Figure 1 shown, for example, a laminate 1a including the low refractive index film 10 can be provided. The laminate 1a includes a substrate 20 and the low refractive index film 10. In the laminate 1a, the low refractive index film 10 is formed along the surface of the substrate 20.
[0064] The low refractive index film 10 is in contact with the surface of the substrate 20, for example.
[0065] As Figure 1 shown, in the laminate 1a, the low refractive index film 10 is formed in contact with one main surface of the substrate 20, for example. The low refractive index film 10 can also be formed in contact with both main surfaces of the substrate 20, for example.
[0066] The substrate 20 may be a plate-like component having a flat surface, a component such as a lens having a curved surface, a component such as a diffraction grating having a surface having concavoconvexities, or a component such as a microlens array and a diffuser having a surface having fine concavoconvexities. The substrate 20 may also be a component having a surface defined by a combination of these surfaces.
[0067] The substrate 20 is an article or a part of an article coated with a low refractive index film or an anti-reflection film, but is not limited to articles with specific functions. The substrate 20 can be, for example, an optical element such as a lens, a reflector, a prism, a diffuser, a flat microlens array, a polarizing element, a diffraction grating, a hologram, a light modulating element, a light deflecting element, and a filter (including an acousto-optic element), a solid-state imaging device, a window or windshield of a building or a car, a light-transmitting shield such as a helmet and goggles, a display device such as a display screen and a screen. When the low refractive index film 10 is used for anti-reflection, it is easy to improve the transmittance of light in the laminate 1a.
[0068] like Figure 1 As shown, the base material 20 includes, for example, a plate-shaped substrate 21 having two main surfaces facing opposite sides. The material of the substrate 21 is not limited to a specific material. The material of the substrate 21 is, for example, glass, resin, or semiconductor materials such as silicon. Examples of glass are soda glass, borosilicate glass, aluminoborosilicate glass, fluorophosphate glass, phosphate glass, and multi-component optical glass with improved optical properties such as refractive index. Examples of resins are polyolefin resins, polycarbonate resins, polyamide resins, epoxy resins, acrylic resins, polyether resins, polyimide resins, polyurethane resins, and silicone resins.
[0069] The arithmetic mean roughness Ra of the surface of the substrate 20 determined according to Japanese Industrial Standard (JIS) B 0601-1994 is not limited to a specific value. The arithmetic mean roughness Ra of the surface of the substrate 20 is, for example, 0.3 nm or more and 140 nm or less. By making the arithmetic mean roughness Ra of the surface of the substrate 20 more than 0.3 nm, the adhesion of the substrate 20 and the low refractive index film 10 is easy to become good. Therefore, even if the first layer 11 has pores 15, the low refractive index film 10 is not easy to peel off from the substrate 20. By making the arithmetic mean roughness Ra of the surface of the substrate 20 less than 140 nm, the film thickness of the low refractive index film 10 is not easy to be uneven in space, and the function that the low refractive index film 10 should play is not easy to be uneven in the plane. In addition, in the laminate 1a, it is possible to prevent the effective reduction of the transmittance of light due to phenomena such as scattering of light.
[0070] The arithmetic mean roughness Ra of the surface of the substrate 20 is preferably from 0.4 nm to 100 nm, more preferably from 0.5 nm to 50 nm, and even more preferably from 0.5 nm to 35 nm.
[0071] The arithmetic mean roughness Ra of the surface of the substrate 20 and the wavelength λ of the incident light toward the laminate 1a i [nm] For example, Ra≤λ i / 4. As a result, light scattering is less likely to occur in the laminate 1a. For example, when the incident light is visible light having a wavelength of 550nm, by satisfying the relationship Ra≤550 / 4[nm]=137.5nm, a decrease in transmittance due to light scattering can be prevented.
[0072] The arithmetic mean roughness Ra of the surface of the substrate 20 and the average particle size d of the hollow particles 13 e For example, if Ra≤d e As a result, the hollow particles 13 in the low refractive index film 10 are easily dispersed uniformly. For example, when the average particle size d of the hollow particles 13 is e When it is 50 nm, it is preferable to satisfy the relationship of Ra≤50 nm.
[0073] The contact angle α of a water droplet on the substrate 20 surface is not limited to a specific value. On the other hand, by adjusting the wettability of the substrate 20 surface, pores 15 are easily formed near the interface between the low refractive index film 10 and the substrate 20 in the low refractive index film 10 .
[0074] The contact angle α of the water drop on the surface of the substrate 20 is, for example, 5° or more and 140° or less. By making the contact angle α 5° or more, the liquid composition as the precursor of the low refractive index film 10 on the surface of the substrate 20 is repelled, and the pores 15 can be formed in the first layer 11 in a desired state. By making the contact angle α 140° or less, the liquid composition as the precursor of the low refractive index film 10 on the surface of the substrate 20 can be prevented from being excessively repelled, and the low refractive index film 10 is easy to have a desired film thickness. In addition, it is not easy to generate stripe-shaped defects and uneven film thickness in the low refractive index film 10, and it is easy to exhibit uniform characteristics within the surface of the low refractive index film 10.
[0075] The arithmetic mean roughness Ra of the surface of the substrate 20 and the contact angle α of a water droplet on the surface of the substrate 20 are adjusted, for example, by applying a specific surface treatment to the surface of the substrate 20. An example of a surface treatment method is a method of chemically or physically changing the surface state of the substrate 20 using a treatment based on chemicals or sandblasting. For example, if a method of forming fine concave-convex shapes on the surface of the substrate 20 is used, the liquid composition as a precursor of the low refractive index film 10 is easy to exert a physical bonding effect such as an anchoring effect on the surface of the substrate 20. An example of a surface treatment method may be a method of changing the chemical bonding state of the functional groups on the surface of the substrate 20, such as corona treatment, plasma treatment, ultraviolet irradiation treatment, and flame treatment. By such a method, the wettability of the liquid composition as a precursor of the low refractive index film 10 on the surface of the substrate 20 can also be adjusted. In addition, the wettability of the liquid composition as a precursor of the low refractive index film 10 on the surface of the substrate 20 can also be adjusted by applying a surface treatment agent such as a primer or a silane coupling agent. Furthermore, the arithmetic mean roughness Ra of the surface of the substrate 20 and the contact angle α of a water droplet on the surface of the substrate 20 can be adjusted by forming the surface of the substrate 20 with specific layers such as a functional layer and a base layer.
[0076] The substrate 20 may have a specific functional layer. In this case, the functional layer may be a layer, a film, or a thin film-like functional layer that adjusts the transmittance and reflectivity of light, such as an anti-reflection film, a light absorbing film, and a light reflecting film. The anti-reflection film may be a single-layer or multi-layer dielectric film containing inorganic materials such as SiO2, MgF2, and TiO2. The light reflecting film may be a single-layer or multi-layer dielectric film containing inorganic materials such as SiO2, MgF2, and TiO2. The light reflecting film may be a metal film. The light absorbing film may be a film containing a resin containing an infrared absorber or an ultraviolet absorber. Examples of infrared absorbers include squarylium salt pigments, diimmonium pigments, cyanine pigments, phthalocyanine pigments, azo pigments, and complexes containing metals such as phosphorus oxides and copper. Examples of ultraviolet absorbers include benzophenone pigments, benzotriazole pigments, and triazine pigments. The functional layer may be a layer, a film, or a thin film-like functional layer that adjusts the behavior with respect to water or oil contained in the environment, such as an antifogging film, a water-repellent film, an oil-repellent film, and a hydrophilic film.
[0077] The low refractive index film 10 can be produced, for example, by applying a specific liquid composition on the surface of the substrate 20 to form a coating film and curing the coating film. The liquid composition can be prepared, for example, by mixing the raw materials of the binder 14 with the hollow particles 13. The above-mentioned functional components are added to the liquid composition as needed.
[0078] The liquid composition may include, for example, a solvent and water. Thus, it is easy to achieve the purpose of adjusting the viscosity of the liquid composition, improving the dispersibility of the functional components in the liquid composition, or improving the solubility of the raw materials of the adhesive 14. The solvent is not limited to a specific solvent. Examples of the solvent may be tetrahydrofuran (THF), cyclohexanone, cyclohexane, toluene, xylene, alcohols, phenols, water, glycerol, acetone, methyl ethyl ketone (MEK), diethyl ether, ethyl acetate, and mixtures thereof.
[0079] The liquid composition may contain an acid, for example. When the raw material of the binder 14 contains alkoxysilane, the acid acts as a catalyst for reactions such as hydrolysis of the alkoxysilane. The acid is not limited to a specific acid. Examples of the acid include formic acid and hydrochloric acid.
[0080] The laminate 1a can be modified from various viewpoints. For example, the laminate 1a can also be modified as follows: Figure 2A The laminate 1b shown, Figure 2B The laminate 1c shown, Figure 2C The laminate 1d shown, or Figure 2D The laminate 1b, the laminate 1c, the laminate 1d, and the laminate 1e are formed in the same manner as the laminate 1a except for the parts specially described. The components of the laminate 1b, the laminate 1c, the laminate 1d, and the laminate 1e that are the same as or correspond to the components of the laminate 1a are given the same reference numerals, and detailed descriptions are omitted. The descriptions of the laminate 1a are also applicable to the laminate 1b, the laminate 1c, the laminate 1d, and the laminate 1e as long as there is no technical contradiction.
[0081] like Figure 2A and Figure 2B As shown, the substrate 20 of the laminates 1b and 1c further includes a base layer 22. The surface of one or both main surfaces of the substrate 20 is formed by the base layer 22. In the laminate 1b, the low refractive index film 10 is formed on the base layer 22. The base layer 22 makes it easy to adjust the surface of the substrate 20 to a state suitable for forming the low refractive index film 10. For example, it is easy to adjust the arithmetic mean roughness Ra of the surface of the substrate 20 or the contact angle α of a water droplet on the surface of the substrate 20 to a desired range.
[0082] In the laminate 1 c , a pair of low-refractive-index films 10 are formed on the surfaces of both main surfaces of the substrate 20 . One of the pair of low-refractive-index films 10 is formed on the base layer 22 .
[0083] The base layer 22 is not limited to a specific layer. The base layer 22 includes, for example, at least one of silicon dioxide and silsesquioxane. The base layer 22 may include silicon dioxide, may include silsesquioxane, or may include a mixture of these. The base layer 22 may include inorganic materials such as SiO2, TiO2, and MgF2. The base layer 22 may also be a multilayer film formed by laminating a plurality of layers of these inorganic materials. The base layer 22 may also be a layer containing resins such as polyolefin resins, polycarbonate resins, polyamide resins, epoxy resins, acrylic resins, polyether resins, polyimide resins, polyurethane resins, fluorine resins, and silicone resins.
[0084] like Figure 2A and Figure 2B As shown, the surface of one main surface of the substrate 20 is formed by the base layer 22. On the other hand, the surfaces of both main surfaces of the substrate 20 may be formed by the base layer 22. In this case, a pair of low refractive index films 10 may be formed on the base layer 22 forming the surfaces of both main surfaces of the substrate 20.
[0085] The thickness of the base layer 22 is not limited to a specific thickness. The base layer 22 has a thickness of, for example, 5 to 50 nm.
[0086] like Figure 2C and Figure 2D As shown, the substrate 20 of the laminates 1d and 1e further includes a functional layer 23. The surface of one main surface of the substrate 20 is formed by the functional layer 23. In the laminate 1d, the low refractive index film 10 is formed on the functional layer 23. The desired function can be imparted to the laminates 1d and 1e by the functional layer 23. In addition, the surface of the substrate 20 can be adjusted to a state suitable for forming the low refractive index film 10 by the functional layer 23. For example, the arithmetic mean roughness Ra of the surface of the substrate 20 or the contact angle α of a water droplet on the surface of the substrate 20 can be easily adjusted to a desired range by the functional layer 23.
[0087] In the laminate 1 e , a pair of low-refractive-index films 10 are formed on the surfaces of both main surfaces of the substrate 20 . One of the pair of low-refractive-index films 10 is formed on the functional layer 23 .
[0088] The functional layer 23 is not limited to a specific layer as long as it has a specific function. The functional layer 23 is, for example, a layer, film or thin film-shaped functional layer that adjusts the transmittance and reflectivity of light, such as an anti-reflection film, a light absorbing film and a light reflecting film. The anti-reflection film is, for example, a film composed of a single layer or multiple layers of inorganic materials such as SiO2, MgF2 and TiO2. The light reflecting film may, for example, include a film composed of a single layer or multiple layers of inorganic materials such as SiO2, MgF2 and TiO2, or a metal film composed of a metal. The light absorbing film is, for example, a film containing a resin containing an infrared absorber or an ultraviolet absorber. Examples of infrared absorbers are squarylium salt pigments, diimmonium pigments, cyanine pigments, phthalocyanine pigments, azo pigments, and complexes containing metals such as phosphorus oxides and copper. Examples of ultraviolet absorbers are benzophenone pigments, benzotriazole pigments and triazine pigments. The light absorbing film may include a metal film composed of a metal.
[0089] The functional layer 23 may be a layer, a film, or a thin film-like functional layer that adjusts the behavior against water or oil contained in the environment, such as an antifog film, a waterproof film, an oil-repellent film, and a hydrophilic film. In other words, the laminates 1d and 1e may include a substrate 20, at least one of an antifog film, a waterproof film, an oil-repellent film, and a hydrophilic film formed on the substrate 20, and a low refractive index film 10.
[0090] like Figure 2C and Figure 2D As shown, the surface of one main surface of the substrate 20 is formed by the functional layer 23. On the other hand, the surfaces of both main surfaces of the substrate 20 may be formed by the functional layer 23. In this case, the low refractive index film 10 may be formed on the functional layer 23 forming the surfaces of both main surfaces of the substrate 20.
[0091] Various articles having a low refractive index film 10 can be provided. For example, an optical element having a surface formed by the low refractive index film 10 can be provided. In addition, a windproof material having a low refractive index film 10 can also be provided. Examples of windproof materials are window glass and windshields. In addition, a display device having a low refractive index film 10 can also be provided.
[0092] Example
[0093] The present invention is described in more detail by way of examples. It should be noted that the present invention is not limited to the following examples. First, the evaluation methods related to the examples and comparative examples are described.
[0094] <Evaluation of film-forming properties>
[0095] The film-forming property of the liquid composition for low refractive index film of each embodiment and each comparative example on the substrate surface of each embodiment and each comparative example was evaluated. When it was confirmed that there was an uncoated portion when the liquid composition for low refractive index film was applied to the substrate surface, or the thickness of the low refractive index film was uneven, the film-forming property was evaluated as "F". On the other hand, when these situations were not confirmed, the film-forming property was evaluated as "A". The results are shown in Table 2.
[0096] <Reflectivity, Refractive Index, and Film Thickness>
[0097] Using a spectrophotometer (manufactured by Hitachi High-Technologies Corporation, product name: U-4000), the incident angle was adjusted to 12 °, and the spectral reflectivity of the laminate of each embodiment and each comparative example was measured. Further, the optical thin film design software FilmWizard (manufactured by Scientific Computing International) was used to obtain the refractive index and film thickness of the low refractive index film of each embodiment and each comparative example. The spectral reflectivity, refractive index and film thickness under the D line (wavelength 589nm) are shown in Table 2. In addition, as a laminate for spectral reflectivity measurement, the following laminate can be used, that is, in the case of forming a low refractive index film on one main surface of the substrate, by making the main surface where the low refractive index film is not formed into a rough surface with black coating on its entire surface, or making a matte surface, etc., the influence of reflection caused by the main surface can be ignored. In this case, the black coating is not limited to a specific coating, and can be an ink coating (ink coating) or a coating used in the optical field known as flare cut. As a black coating, for example, GT-1000, GT-2000, GT-7 and CS-37 manufactured by Canon Chemical Co., Ltd. can be used. The matte surface is formed, for example, using a grinding material having a particle size of #500 (No. 500) or more. The main surface processed into a matte surface can also be coated in black thereafter. In the case where the laminate includes a base layer, the film thickness of the base layer is measured by reflection spectroscopy using a film thickness measurement system F20-UV manufactured by Filmetrics before forming the low refractive index film.
[0098] <Haze>
[0099] The haze of the laminate of each Example and each Comparative Example was measured at three locations 1 cm apart from each other using a haze meter (manufactured by SUGA TEST INSTRUMENTS, product name: HZ-V3), and the average value was determined as the haze of each Example and Comparative Example.
[0100] <Number of pores Nv and porosity Vv1>
[0101] In order to confirm the state of pores in the low refractive index film of the laminate of each example and each comparative example, first, along the cross-section parallel to the normal of the substrate surface, a Focused Ion Beam System SMI3200F manufactured by SII Nanotechnology Inc. was used to cut at a thickness of 100 nm. Carbon with a thickness of 400 - 500 nm was vapor-deposited on the outermost surface to prepare a specimen. The cross-section of this specimen was subjected to bright-field transmission observation under a magnification of 250,000 times using a Scanning Transmission Electron Microscope (STEM) S-5500 manufactured by Hitachi High-Technologies Corporation, and a transmission photographed image of the laminate including the low refractive index film was obtained. The acceleration voltage was 200 kV. In the transmission photographed image of the laminate, white protruding pores were observed. After digitizing the obtained transmission photographed image of the laminate cross-section with 0 - 255 gray levels, histogram equalization processing was performed to obtain an image with a certain contrast. Then, gray levels of 229 - 255 were regarded as pores. The calculation of the number, number density, and cross-sectional area of the pores was carried out as follows. First, for the transmission photographed image of the laminate cross-section, an image of 1000 nm (1 μm) was obtained along the direction parallel to the substrate surface, and the pores were determined based on the above method. Figure 4 The figure shows the transmission photographed image of the laminate cross-section and the determined pores. Figure 4 In this figure, in order to be easily distinguishable from other parts, the pores are shown in black. Then, the thickness dt of the low refractive index film was measured, the thickness d1 of the first layer was obtained, and the area At1 of the cross-section S1 of the first layer was obtained by the operation of d1 × 1000. When 70 nm ≤ dt ≤ 400 nm for the thickness d1 of the first layer, d1 = dt / 2; when dt > 400 nm, d1 = 200 nm. For the pores with a cross-sectional area of 1000 nm 2 or more in the cross-section S1 of the first layer, the number Nv1 was counted, and the sum Av1 of the cross-sectional areas of the pores with a cross-sectional area of 1000 nm 2 or more was calculated. Similarly, the area At2 of the cross-section S2 of the second layer (= (dt - d1) × 1000) was calculated. For the pores with a cross-sectional area of 1000 nm 2 or more in the cross-section S2 of the second layer, the number Nv2 was counted, and the sum of the cross-sectional areas of the pores with a cross-sectional area of 1000 nm 2The sum of the cross-sectional areas of the above pores Av2. Divide the number of pores Nv1 by the area At1 to find the number density ρv1. In addition, the sum of the cross-sectional areas of the pores Av1 is divided by the area At1 to determine the porosity Vv1. In each embodiment, the transmission images of the laminate are obtained at three positions 10 mm apart in the plane, and the above parameters are respectively calculated, and their average values are adopted. For the values of the number of pores Nv and the area ratio of the pores Vv[%], the values below the decimal point are adopted. For the above calculations, when necessary, the image processing software ImageJ version 1.51 provided by the National Institutes of Health of the United States is used for performance.
[0102] <Abrasion resistance test>
[0103] The laminates of each example and each comparative example were subjected to a 50 g / cm 2 Under the load of , the surface of the laminate was moved back and forth 5 times using a cotton cloth Clint manufactured by Asahi Kasei Chemicals. The reflectivity under D line (wavelength = 589nm) was then measured, and the difference in reflectivity before and after the abrasion resistance test was compared. D , ΔR D / (Reflectivity R under D line before abrasion resistance test D )≤25% is evaluated as "A", and ΔR D / (Reflectivity R under D line before abrasion resistance test D )>25% was evaluated as "F".
[0104] <Example 1>
[0105] 0.6 g of tetraethoxysilane (TEOS) (manufactured by Tokyo Chemical Industry Co., Ltd.), 1.18 g of methyltriethoxysilane (MTES) (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.82 g of 0.3% by mass formic acid (manufactured by Kishida Chemical Co., Ltd.), 3 g of sol containing hollow silica particles (manufactured by JGC Catalysts & Chemicals Co., Ltd., product name: Thrulya 4110), and 22.4 g of ethanol (manufactured by Kishida Chemical Co., Ltd.) were mixed and reacted at 35°C for 3 hours. The sol containing hollow silica particles used contains a solvent, contains 25% by mass of hollow silica as a solid component, and the average particle size of the hollow silica particles in the particle size distribution based on the number is about 50 nm. The thickness of the shell formed by silica of the hollow silica particles is 10 to 20 nm. The maximum size of the internal space of the hollow silica particles is about 10 to 30 nm. The refractive index of the hollow particles is 1.25. Thus, the liquid composition for low refractive index film of Example 1 was obtained. In the liquid composition for low refractive index film of Example 1, the content of solid components from TEOS was converted into 0.6% by mass of silicon dioxide, the content of methylsilsesquioxane (MeSq) from MTES was 1.6% by mass, and the content of hollow silica particles was 2.6% by mass. In the solid components of the liquid composition for low refractive index film of Example 1, on a mass basis, silicon dioxide from TEOS contained 13%, MeSq from MTES contained 33%, and hollow silica particles contained 54%. It should be noted that, with respect to the content of hollow silica particles, the solid component in the sol containing hollow silica particles was 25% by mass, and the solid component was assumed to be hollow silica particles to obtain the content. In addition, the ratio of the amount of MTES added in the preparation of the liquid composition for low refractive index film of Example 1 to the amount of TEOS was 7 / 3.
[0106] Using an ultrasonic cleaner (manufactured by Emerson Japan, model: Bransonic 5510-J-DTH, output: 135W), a glass substrate made of soda lime glass (size: 40mm×40mm, thickness: 1mm, double-sided polished, refractive index: 1.52) was cleaned in ultrapure water for 15 minutes. Thereafter, the glass substrate was cleaned in a commercially available alkaline cleaning solution (2% dilution of Semi Clean L.GL, manufactured by Yokohama Oil & Fats Industry Co., Ltd.) for 15 minutes, and then cleaned in ultrapure water for 15 minutes. Thereafter, a corona surface treatment device (manufactured by Shinko Electric Instrumentation Co., Ltd., model: Corona Master PS-1M) was used to corona treat the surface of the glass substrate with an output of 14kV. The contact angle of water droplets on the surface of the glass substrate after corona treatment was 2°. The glass substrate was stored in a clean bench of less than 100 at a temperature of 23 to 25°C and a relative humidity of 50 to 60% for 12 hours. In this way, the substrate of Example 1 was produced. As shown in Table 1, the contact angle of the water droplet on the substrate surface of Example 1 is 32°, and the arithmetic mean roughness Ra of the substrate surface of Example 1 is 0.5 nm. The contact angle of the water droplet is measured using a contact angle meter manufactured by ASUMI GIKEN. The arithmetic mean roughness Ra is determined based on the measurement results obtained using an atomic force microscope SPI3700 manufactured by SEIKO Electronics in a cyclic contact mode in accordance with JIS B 0601-1994. This is also the same in other embodiments and comparative examples.
[0107] The liquid composition for the low refractive index film of Example 1 is applied to one main surface of the substrate of Example 1 by spin coating to form a coating. The coating has a good and uniform appearance. Thereafter, the substrate with the coating is placed in an oven maintained at 200°C for 10 minutes to dry the coating to obtain the low refractive index film of Example 1. Thus, a laminate of Example 1 having a substrate and a low refractive index film formed on the substrate is obtained. The appearance of the low refractive index film of Example 1 is observed, and the result shows that it has a uniform thickness. After grinding the surface of the substrate of the laminate of Example 1 on which the low refractive index film is not formed to make a matte surface, the spectral reflectance is measured. It can be found that the reflectivity of the laminate of Example 1 under the D line (wavelength 589nm) is 0.53%, the film thickness of the low refractive index film of Example 1 is 121nm, and the refractive index is 1.16. The mass of silica, silsesquioxane and hollow silica particles constituting the binder in the low refractive index film of Example 1 was determined assuming that the mass of the corresponding components contained in the solid content of the liquid composition of Example 1 was equal.
[0108] <Example 2>
[0109] The liquid composition for low refractive index film of Example 2 was prepared in the same manner as Example 1 except for the following aspects. The ratio of the mass of each component of the liquid composition for low refractive index film to the mass of the entire solid component was assumed to be equal to the ratio of the mass of each component to the mass of the low refractive index film, and the addition amounts of TEOS, MTES, and the sol containing hollow silica particles were adjusted so that the ratio of the mass of each component to the mass of the low refractive index film was the value shown in Table 2.
[0110] 0.6 g of tetraethoxysilane (TEOS) (manufactured by Tokyo Chemical Industry Co., Ltd.), 1.18 g of methyltriethoxysilane (MTES) (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.82 g of 0.3 mass % formic acid (manufactured by Kishida Chemical Co., Ltd.), and 22.4 g of ethanol (manufactured by Kishida Chemical Co., Ltd.) were mixed and reacted at 35° C. for 3 hours. Ethanol was then added to the mixed solution to adjust the total solid content of silicon dioxide derived from TEOS and methylsilsesquioxane (MeSq) derived from MTES to 3 mass %, thereby obtaining a liquid composition B for a base layer.
[0111] On one main surface of a glass substrate (size: 40 mm × 40 mm, thickness: 1 mm, refractive index: 1.52) composed of float glass and pre-cleaned by alkali cleaning, a liquid composition B for base layer was applied by spin coating to form a coating film. Then, the coating film was dried at 200° C. and 10 minutes inside an oven to form a base layer B2. The substrate of Example 2 was obtained. The thickness of base layer B2 was 13 nm. The contact angle of a water droplet on the surface of base layer B2 was 45°, and the arithmetic mean roughness Ra of the surface of base layer B2 was 17 nm.
[0112] The liquid composition for the low refractive index film of Example 2 is applied to the surface of the base layer B2 of the substrate of Example 2 by spin coating to form a coating. The coating has a good and uniform appearance just after coating. Thereafter, the substrate of Example 2 is placed in an oven maintained at 200°C for 10 minutes to dry the coating to form a low refractive index film of Example 2. Thus, a laminate of Example 2 having a substrate and a low refractive index film formed on the substrate is obtained. By observing the appearance of the low refractive index film of Example 2, the low refractive index film of Example 2 has a uniform thickness. After grinding the surface of the substrate of the laminate of Example 2 where the low refractive index film is not formed to make a matte surface, the spectral reflectance is measured. In addition, the film thickness of the base layer B2 is about 10 nm, and the refractive index is almost unchanged from the glass as the substrate, so it is believed that the base layer B2 has almost no effect on the reflectivity of the laminate. Based on the obtained spectral reflectance, the reflectance of the laminate under line D was calculated to be less than 0.1%, and the film thickness of the low refractive index film of Example 2 was 121 nm, and the refractive index was 1.23. In the low refractive index film of Example 2, on a mass basis, the silica constituting the binder contained 23%, the silsesquioxane contained 57%, and the hollow silica particles contained 20%.
[0113] <Example 3>
[0114] The liquid composition for low refractive index film of Example 3 was prepared in the same manner as in Example 1 except for the following aspects. The ratio of the mass of each component of the liquid composition for low refractive index film to the mass of the entire solid component was assumed to be equal to the ratio of the mass of each component to the mass of the low refractive index film, and the addition amounts of TEOS, MTES, and the sol containing hollow silica particles were adjusted so that the ratio of the mass of each component to the mass of the low refractive index film was the value shown in Table 2.
[0115] The same base layer liquid composition B as in Example 2 was applied by spin coating on both main surfaces of a glass substrate (size: 40 mm×40 mm, thickness: 1 mm, refractive index: 1.52) composed of float glass and cleaned in advance by alkali cleaning to form a coating film. Next, the coating film was dried in an oven at 200° C. for 10 minutes to form a base layer B3, thereby obtaining a substrate of Example 3. The thickness of the base layer B3 was 13 nm. The contact angle of a water droplet on the surface of the base layer B3 was 43°, and the arithmetic mean roughness Ra of the surface of the base layer B3 was 11 nm.
[0116] The liquid composition for the low refractive index film of Example 3 is applied to the surface of the base layer B3 of the substrate of Example 3 by spin coating to form a coating. The coating has a good and uniform appearance just after coating. Thereafter, the substrate of Example 3 is placed in an oven maintained at 200°C for 10 minutes to dry the coating to form a low refractive index film of Example 3. Thus, a laminate of Example 3 having a substrate and a low refractive index film formed on the substrate is obtained. By observing the appearance of the low refractive index film of Example 3, the low refractive index film of Example 3 has a uniform thickness. As in the case of Example 1, after measuring the spectral reflectance of the laminate of Example 3, each parameter is calculated. The reflectance of the laminate of Example 3 under the D line is 0.25%, the film thickness of the low refractive index film of Example 3 is 120nm, and the refractive index is 1.19. In the low refractive index film of Example 3, on a mass basis, the silica constituting the binder contains 19%, the silsesquioxane contains 51%, and the hollow silica particles contain 30%.
[0117] <Example 4>
[0118] The liquid composition for low refractive index film of Example 4 was prepared in the same manner as in Example 1 except for the following aspects. The ratio of the mass of each component of the liquid composition for low refractive index film to the mass of the entire solid component was assumed to be equal to the ratio of the mass of each component to the mass of the low refractive index film, and the addition amounts of TEOS, MTES, and the sol containing hollow silica particles were adjusted so that the ratio of the mass of each component to the mass of the low refractive index film was the value shown in Table 2.
[0119] The same base layer liquid composition B as in Example 2 was applied by spin coating on one main surface of a glass substrate (size: 40 mm×40 mm, thickness: 1 mm, refractive index: 1.52) composed of float glass and cleaned in advance by alkali cleaning to form a coating film. Next, the coating film was dried in an oven at 200° C. for 10 minutes to form a base layer B4, thereby obtaining a substrate of Example 4. The thickness of the base layer B4 was 11 nm. The contact angle of a water droplet on the surface of the base layer B4 was 42°, and the arithmetic mean roughness Ra of the surface of the base layer B4 was 13 nm.
[0120] The liquid composition for the low refractive index film of Example 4 is applied to the surface of the base layer B4 of the substrate of Example 4 by spin coating to form a coating. The coating has a good and uniform appearance just after coating. Thereafter, the substrate of Example 4 is placed in an oven maintained at 200°C for 10 minutes to dry the coating to form a low refractive index film of Example 4. Thus, a laminate of Example 4 having a substrate and a low refractive index film formed on the substrate is obtained. By observing the appearance of the low refractive index film of Example 4, the low refractive index film of Example 4 has a uniform thickness. As in the case of Example 1, the spectral reflectance of the laminate of Example 4 is measured and each parameter is calculated. The reflectance of the laminate of Example 4 under line D is 0.62%, the film thickness of the low refractive index film of Example 4 is 123nm, and the refractive index is 1.15. In the low refractive index film of Example 4, on a mass basis, the silica constituting the binder contains 17%, the silsesquioxane contains 43%, and the hollow silica particles contain 40%.
[0121] <Example 5>
[0122] The liquid composition for low refractive index film of Example 5 was prepared in the same manner as in Example 1 except for the following aspects. The ratio of the mass of each component of the liquid composition for low refractive index film to the mass of the entire solid component was assumed to be equal to the ratio of the mass of each component to the mass of the low refractive index film, and the addition amounts of TEOS, MTES, and the sol containing hollow silica particles were adjusted so that the ratio of the mass of each component to the mass of the low refractive index film was the value shown in Table 2.
[0123] The same base layer liquid composition B as in Example 2 was applied by spin coating on one main surface of a glass substrate (size: 40 mm × 40 mm, thickness: 1 mm, refractive index: 1.52) composed of float glass and cleaned in advance by alkali cleaning to form a coating film. Next, the coating film was dried in an oven at 200°C for 10 minutes to form a base layer B5, thereby obtaining a substrate of Example 5. The thickness of the base layer B5 was 11 nm. The contact angle of a water droplet on the surface of the base layer B5 was 44°, and the arithmetic mean roughness Ra of the surface of the base layer B5 was 16 nm.
[0124] The liquid composition for the low refractive index film of Example 5 is applied to the surface of the base layer B5 of the substrate of Example 5 by spin coating to form a coating. The coating has a good and uniform appearance just after coating. Thereafter, the substrate of Example 5 is placed in an oven maintained at 200°C for 10 minutes to dry the coating to form a low refractive index film of Example 5. Thus, a laminate of Example 5 having a substrate and a low refractive index film formed on the substrate is obtained. By observing the appearance of the low refractive index film of Example 5, the low refractive index film of Example 5 has a uniform thickness. As in the case of Example 1, the spectral reflectance of the laminate of Example 5 is measured and each parameter is calculated. The reflectance of the laminate of Example 5 under the D line is 1.13%, the film thickness of the low refractive index film of Example 5 is 121nm, and the refractive index is 1.12. In the low refractive index film of Example 5, on a mass basis, the silica constituting the binder contains 14%, the silsesquioxane contains 36%, and the hollow silica particles contain 50%.
[0125] <Example 6>
[0126] The liquid composition for low refractive index film of Example 6 was prepared in the same manner as in Example 1 except for the following aspects. The ratio of the mass of each component of the liquid composition for low refractive index film to the mass of the entire solid component was assumed to be equal to the ratio of the mass of each component to the mass of the low refractive index film, and the addition amounts of TEOS, MTES, and the sol containing hollow silica particles were adjusted so that the ratio of the mass of each component to the mass of the low refractive index film was the value shown in Table 2.
[0127] The same base layer liquid composition B as in Example 2 was applied by spin coating on both main surfaces of a glass substrate (size: 40 mm × 40 mm, thickness: 1 mm, refractive index: 1.52) composed of float glass and cleaned in advance by alkali cleaning to form a coating film. Next, the coating film was dried in an oven at 200° C. for 10 minutes to form a base layer B6, thereby obtaining a substrate of Example 6. The thickness of the base layer B6 was 14 nm. The contact angle of a water droplet on the surface of the base layer B6 was 41°, and the arithmetic mean roughness Ra of the surface of the base layer B6 was 12 nm.
[0128] The liquid composition for the low refractive index film of Example 6 is applied to the surface of the base layer B6 of the substrate of Example 6 by spin coating to form a coating. The coating has a good and uniform appearance just after coating. Thereafter, the substrate of Example 6 is placed in an oven maintained at 200°C for 10 minutes to dry the coating to form a low refractive index film of Example 6. Thus, a laminate of Example 6 having a substrate and a low refractive index film formed on the substrate is obtained. By observing the appearance of the low refractive index film of Example 6, the low refractive index film of Example 6 has a uniform thickness. As in the case of Example 1, the spectral reflectance of the laminate of Example 6 is measured and each parameter is calculated. The reflectance of the laminate of Example 6 under the D line is 1.50%, the film thickness of the low refractive index film of Example 6 is 122nm, and the refractive index is 1.10. In the low refractive index film of Example 6, on a mass basis, the silica constituting the binder contains 8%, the silsesquioxane contains 22%, and the hollow silica particles contain 70%.
[0129] <Example 7>
[0130] 97 g of ethanol was added to 3 g of n-octyltrichlorosilane (manufactured by Tokyo Chemical Industry Co., Ltd.) to obtain a liquid composition C for a base layer.
[0131] The liquid composition C for the base layer was applied by spin coating on one main surface of a glass substrate (size: 40 mm × 40 mm, thickness: 1 mm, refractive index: 1.52) composed of float glass and cleaned in advance by alkali cleaning to form a coating film. Next, the coating film was dried at 200° C. for 10 minutes in an oven to form a base layer C7, thereby obtaining a substrate of Example 7. The thickness of the base layer C7 was 13 nm. The contact angle of a water droplet on the surface of the base layer C7 was 64°, and the arithmetic mean roughness Ra of the surface of the base layer C7 was 23 nm.
[0132] The surface of the base layer C7 of the substrate of Example 7 is coated with the same liquid composition for low refractive index film as in Example 1 by spin coating to form a coating film. The coating film immediately after coating has a good and uniform appearance. Thereafter, the substrate of Example 7 is placed in an oven maintained at 200°C for 10 minutes to dry the coating film and form a low refractive index film of Example 7. Thus, a laminate of Example 7 having a substrate and a low refractive index film formed on the substrate is obtained. By observing the appearance of the low refractive index film of Example 7, the low refractive index film of Example 7 has a uniform thickness. As in the case of Example 1, the spectral reflectance of the laminate of Example 7 is measured and each parameter is calculated. The reflectance of the laminate of Example 7 under the D line is 0.45%, the film thickness of the low refractive index film of Example 7 is 119nm, and the refractive index is 1.17. In the low refractive index film of Example 7, on a mass basis, the silica constituting the binder contains 13%, the silsesquioxane contains 33%, and the hollow silica particles contain 54%.
[0133] <Example 8>
[0134] 97 g of ethanol was added to 3 g of 1H,1H,2H,2H-perfluorooctyltrichlorosilane (manufactured by Tokyo Chemical Industry Co., Ltd.) to obtain a liquid composition D for a base layer.
[0135] On one main surface of a glass substrate (size: 40 mm × 40 mm, thickness: 1 mm, refractive index: 1.52) composed of float glass and pre-cleaned by alkali cleaning, a liquid composition D for base layer was applied by spin coating to form a coating film. Next, the coating film was dried at 200° C. for 10 minutes in an oven to form a base layer D8, thereby obtaining a substrate of Example 8. The thickness of the base layer D8 was 11 nm. The contact angle of a water droplet on the surface of the base layer D8 was 118°, and the arithmetic mean roughness Ra of the surface of the base layer D8 was 35 nm.
[0136] The surface of the base layer D8 of the substrate of Example 8 is coated with the same liquid composition for low refractive index film as in Example 1 by spin coating to form a coating film. The coating film immediately after coating has a good and uniform appearance. Thereafter, the substrate of Example 8 is placed in an oven maintained at 200°C for 10 minutes to dry the coating film and form a low refractive index film of Example 8. Thus, a laminate of Example 8 having a substrate and a low refractive index film formed on the substrate is obtained. By observing the appearance of the low refractive index film of Example 8, the low refractive index film of Example 8 has a uniform thickness. As in the case of Example 1, the spectral reflectance of the laminate of Example 8 is measured and each parameter is calculated. The reflectance of the laminate of Example 8 under the D line is 0.55%, the film thickness of the low refractive index film of Example 8 is 120nm, and the refractive index is 1.16. In the low refractive index film of Example 8, on a mass basis, the silica constituting the binder contains 13%, the silsesquioxane contains 33%, and the hollow silica particles contain 54%.
[0137] <Example 9>
[0138] Using an ultrasonic cleaner, a polycarbonate (PC) substrate (manufactured by AS-1, part number: PCC0050503, size: 40mm×40mm, thickness: 1mm, refractive index: 1.59) was cleaned in ultrapure water for 15 minutes. Thereafter, the PC substrate was cleaned with a commercially available alkaline cleaning solution for 15 minutes, and further cleaned in ultrapure water for 15 minutes. Next, the surface of the PC substrate was corona treated for 10 minutes using a corona surface treatment device (manufactured by Shinko Electric Instrumentation Co., Ltd., model: Corona Master PS-1M) with an output of 14kV under the same method and conditions as in Example 1 to obtain the substrate of Example 9. The contact angle of water droplets on the surface of the PC substrate after the corona treatment was 19°, and the arithmetic mean roughness Ra of the PC substrate surface after the corona treatment was 34nm.
[0139] The same liquid composition for low refractive index film as in Example 1 was applied to one main surface of the substrate of Example 9 by spin coating. The coating film immediately after coating had a good and uniform appearance. Thereafter, the substrate of Example 9 was placed in an oven maintained at 200°C for 10 minutes to dry the coating film and form a low refractive index film of Example 9. Thus, a laminate of Example 9 having a substrate and a low refractive index film formed on the substrate was obtained. By observing the appearance of the low refractive index film of Example 9, the low refractive index film of Example 9 had a uniform thickness. As in the case of Example 1, the spectral reflectance of the laminate of Example 9 was measured and each parameter was calculated. The reflectance of the laminate of Example 9 under line D was 0.57%, the thickness of the low refractive index film of Example 9 was 122nm, and the refractive index was 1.18. In the low refractive index film of Example 9, on a mass basis, the silica constituting the binder contained 13%, the silsesquioxane contained 33%, and the hollow silica particles contained 54%.
[0140] <Example 10>
[0141] Using an ultrasonic cleaner, a substrate of the same type as the PC substrate used in Example 9 was cleaned in ultrapure water for 15 minutes. Thereafter, the PC substrate was cleaned with a commercially available alkaline cleaning solution for 15 minutes and further cleaned in ultrapure water for 15 minutes. Next, the treatment time was adjusted to 1 minute, and the corona treatment was performed using the same method and conditions as in Example 1 to obtain the substrate of Example 10. The contact angle of a water drop on the surface of the PC substrate after the corona treatment was 37°, and the arithmetic mean roughness Ra of the surface of the PC substrate after the corona treatment was 27 nm.
[0142] The same liquid composition for low refractive index film as in Example 1 is applied to one main surface of the substrate of Example 10 by spin coating. The coating film immediately after coating has a good and uniform appearance. Thereafter, the substrate of Example 10 is placed in an oven maintained at 200°C for 10 minutes to dry the coating film and form a low refractive index film of Example 10. Thus, a laminate of Example 10 having a substrate and a low refractive index film formed on the substrate is obtained. By observing the appearance of the low refractive index film of Example 10, the low refractive index film of Example 10 has a uniform thickness. As in the case of Example 1, the spectral reflectance of the laminate of Example 10 is measured, and the various parameters are calculated. The reflectance of the laminate of Example 10 under the D line is 0.73%, and the film thickness of the low refractive index film of Example 10 is 121nm, and the refractive index is 1.17. As shown in Table 2, in the low refractive index film of Example 10, on a mass basis, silica constituting the binder contained 13%, silsesquioxane contained 33%, and hollow silica particles contained 54%.
[0143] <Example 11>
[0144] Using an ultrasonic cleaner, a substrate of the same type as the substrate made of PC used in Example 9 was cleaned in ultrapure water for 15 minutes. Thereafter, the substrate made of PC was cleaned with a commercially available alkaline cleaning solution for 15 minutes, and further cleaned in ultrapure water for 15 minutes to obtain a substrate of Example 11. The contact angle of a water drop on the surface of the substrate of Example 11 was 71°, and the arithmetic mean roughness Ra of the surface of the substrate of Example 11 was 21 nm.
[0145] The same liquid composition for low refractive index film as in Example 1 is applied to one main surface of the substrate of Example 11 by spin coating. The coating film immediately after coating has a good and uniform appearance. Thereafter, the substrate of Example 11 is placed in an oven maintained at 200°C for 10 minutes to dry the coating film and form a low refractive index film of Example 11. Thus, a laminate of Example 11 having a substrate and a low refractive index film formed on the substrate is obtained. By observing the appearance of the low refractive index film of Example 11, the low refractive index film of Example 11 has a uniform thickness. As in the case of Example 1, the spectral reflectance of the laminate of Example 11 is measured, and the various parameters are calculated. The reflectance of the laminate of Example 11 under the D line is 0.84%, and the film thickness of the low refractive index film of Example 11 is 123nm, and the refractive index is 1.16. As shown in Table 2, in the low refractive index film of Example 11, on a mass basis, silica constituting the binder contained 13%, silsesquioxane contained 33%, and hollow silica particles contained 54%.
[0146] <Comparative Example 1>
[0147] While stirring 99.5 g of decamethylcyclopentasiloxane (manufactured by Shin-Etsu Chemical Co., Ltd., product name KF-995), 0.5 g of tetrachlorosilane (SiCl4) manufactured by Shin-Etsu Chemical Co., Ltd. was added to the decamethylcyclopentasiloxane to prepare a base layer composition E1 having silicon dioxide as a main component. Furthermore, while stirring 98 g of decamethylcyclopentasiloxane, 2 g of heptadecafluorodecyltrichlorosilane (CF3(CF2)7(CH2)2SiCl3) was added to the decamethylcyclopentasiloxane to prepare a base layer composition E2.
[0148] On one main surface of a glass substrate (size: 40 mm × 40 mm, thickness: 1 mm, refractive index: 1.52) composed of float glass and pre-cleaned by alkali cleaning, a base layer composition E1 was applied by flow coating under an environment of a temperature of 25°C and a relative humidity of 30% to form a coating film, and the coating film was allowed to stand for one minute in a wet state. Next, the base layer composition E1 was applied by flow coating on the coating film under the same conditions, and the coating was allowed to stand for one minute in a wet state. Next, from above the wet coating film of the base layer composition E1 on the surface of the glass substrate, a base layer composition E2 was applied by flow coating under the same conditions as the above conditions, and the coating was allowed to stand for one minute in a wet state. Next, the remaining components of the base layer composition on the surface were completely rinsed off with ethanol, and the coating film was naturally dried to form a base layer E14, thereby obtaining the substrate of Comparative Example 1. The base layer E14 has waterproof properties due to the action of the base layer composition E2. In addition, it was confirmed that particulate protrusions and columnar protrusions were formed on the surface of the base layer E14 by the action of the base layer composition E1. The thickness of the base layer E14 was 14 nm. The contact angle of a water droplet on the surface of the base layer E14 was 157°, and the arithmetic mean roughness Ra of the surface of the base layer E14 was 43 nm.
[0149] The low refractive index film liquid composition of Comparative Example 1 was applied by spin coating on the surface of the base layer E14 of the substrate of Comparative Example 1. However, in the substrate of Comparative Example 1, streak-like coating unevenness occurred all over the surface, and a uniform film was not obtained.
[0150] <Comparative Example 2>
[0151] 0.6 g of tetraethoxysilane (TEOS) (manufactured by Tokyo Chemical Industry Co., Ltd.), 1.18 g of methyltriethoxysilane (MTES) (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.82 g of 0.3% by mass formic acid (manufactured by Kishida Chemical Co., Ltd.), 3 g of silica sol (manufactured by Nissan Chemical, product name: Snowtex MP-2040, average particle size: 200 nm), and 22.4 g of ethanol (manufactured by Kishida Chemical Co., Ltd.) were mixed and reacted at 35° C. for 3 hours. Ethanol was added to the reaction solution, and the total solid content of silicon dioxide from tetraethoxysilane and methylsilsesquioxane (MeSq) from methyltriethoxysilane was adjusted to 5% by mass to obtain a liquid composition F for a base layer.
[0152] The liquid composition F for the base layer was applied by spin coating on one main surface of a glass substrate (size: 40 mm × 40 mm, thickness: 1 mm, refractive index: 1.52) composed of float glass and cleaned in advance by alkali cleaning to form a coating film. Next, the coating film was dried at 200° C. for 10 minutes in an oven to form a base layer F15, thereby obtaining a substrate of Comparative Example 2. The thickness of the base layer F15 was 170 nm. The contact angle of a water droplet on the surface of the base layer F15 was 52°, and the arithmetic mean roughness Ra of the surface of the base layer F15 was 150 nm.
[0153] The low refractive index film liquid composition of Comparative Example 1 was applied by spin coating to the surface of the base layer F15 of the substrate of Comparative Example 2. However, in the substrate of Comparative Example 2, streak-like coating unevenness occurred all over the surface, and a uniform film was not obtained.
[0154] [Table 1]
[0155]
[0156]
Claims
1. A laminate comprising a substrate and a low refractive index film in this order, the low refractive index film having a refractive index of 1.01 or more and 1.30 or less.
2. The laminate according to claim 1, wherein the low refractive index film has a first layer and a second layer in this order from the side closer to the substrate, the first layer and the second layer each contain hollow particles and a binder, the first layer has a thickness of half or less of the thickness of the low refractive index film and 200 nm or less, the first layer has pores satisfying at least one of the following conditions (I) and (II), (I) In the cross section of the first layer, there is a 1000 nm 2 The number density of the pores above the cross-sectional area is 5 / μm 2 Above 100 / μm 2 the following, (II) The ratio of the cross-sectional area of the pores in the cross-section to the area of the cross-section of the first layer is 5% or more and 70% or less.
3. The laminate according to claim 2, wherein the first layer has pores satisfying the condition of (I), The cross section of the first layer has a thickness of 1000 nm 2 The number density of the pores having a cross-sectional area of more than 1000 nm is greater than that of the pores having a cross-sectional area of more than 1000 nm in the cross-section of the second layer. 2 The number density of the pores having a cross-sectional area above 1000 Å is large.
4. The laminate according to claim 2 or 3, wherein the first layer has pores satisfying the condition of (II), the ratio of the cross-sectional area of the pores in the cross-section of the first layer to the area of the cross-section of the first layer is higher than the ratio of the cross-sectional area of the pores in the cross-section of the second layer to the area of the cross-section of the second layer.
5. The laminate according to any one of claims 2 to 4, wherein the low refractive index film has a thickness dt of 70 nm or more, with respect to the thickness d1 of the first layer, when 70 nm ≤ dt ≤ 400 nm, the thickness d1 is equal to dt / 2, and when 400 nm < dt, the thickness d1 is equal to 200 nm.
6. The laminate according to any one of claims 2 to 5, wherein the average particle diameter of the hollow particles is 20 nm or more and 100 nm or less.
7. The laminate according to any one of claims 2 to 6, wherein the mass ratio of the binder to the hollow particles is 0.2 or more and 20 or less.
8. The laminate according to any one of claims 1 to 7, wherein the substrate has a surface with a contact angle α of water droplets of 5° or more and 140° or less.
9. The laminate according to any one of claims 2 to 8, wherein the binder contains silica and sesquisiloxane, The mass ratio W of silicon dioxide to the low refractive index film Si 1%≤W Si ≤60%, The mass ratio W of silsesquioxane to the low refractive index film Sq 5% ≤ W Sq ≤90%.
10. The laminate according to claim 9, wherein The mass ratio W of the total amount of silicon dioxide and silsesquioxane to the low refractive index film b 5% ≤ W b ≤90%.
11. The laminate according to any one of claims 2 to 10, wherein The mass ratio W of the hollow particles to the low refractive index film hp It is more than 5% and less than 90%.
12. The laminate according to any one of claims 9 to 11, wherein The mass ratio W of the total amount of silicon dioxide and silsesquioxane to the low refractive index film b The mass ratio W of the hollow particles to the low refractive index film hp 0.2 <W b / W hp <20.
13. The laminate according to any one of claims 1 to 12, wherein the arithmetic mean roughness Ra of the substrate surface is 0.3 nm or more and 140 nm or less.
14. The laminate according to claim 13, wherein The arithmetic mean roughness Ra of the substrate surface is λ i / 4 or less, where λ i It is the wavelength included in the light incident on the laminate, and the unit of the wavelength is nm.
15. The laminate according to any one of claims 1 to 14, wherein a layer containing at least one selected from silica and sesquisiloxane is further provided between the substrate and the low refractive index film.
16. An optical element comprising the laminate according to any one of claims 1 to 15.
17. A method for producing a laminate according to any one of claims 1 to 15, comprising: A liquid composition containing a binder and hollow particles is coated on the surface of a substrate having a surface with a contact angle of water of 5° or more and 140° or less.
18. A method for producing a laminate according to claim 15, wherein: Including: forming a layer comprising at least one of silicon dioxide and silsesquioxane on a surface of a substrate; as well as A liquid composition including a binder and hollow particles is coated on the surface of the layer.
19. The manufacturing method according to claim 18, wherein: The layer has a surface having a contact angle of water of 5° or more and 140° or less.
Citation Information
Patent Citations
Antireflection film and manufacturing method thereof
JP2012108320A
Optical element, and optical system and optical equipment using the same
JP2013033124A